Ven Donate Box / Muhammad Izzul Hafiz Baharuddin - Baharuddin, Muhammad Izzul Hafiz (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Ven Donate Box has storage to store face masks. This product is to help homeless people or people who can't afford to buy a face mask and want to cultivate the practice of helping people. Ven Donate Box is a product that has storage to keep a clean new face mask. It is suitable to help people who cannot afford face masks or homeless people. The function of this product is to have a large enough storage to store face masks that have been packed with plastic and can donate and refill face masks. Meanwhile, the product also has a divided color area made of plastic and made of wood. The objective of Ven Donate Box is to help people who are burdened and cannot afford to buy face masks in stores. It also expands the practice of helping each other among human beings and keeping clean face masks to give those who are difficult or unable to buy. It expects that, with this invention, homeless people can get face masks that are already clean and provide convenience to people who cannot afford to buy face masks in stores. One of the benefits of using this product is to help each other as human beings to avoid this outbreak of covid disease 19. Ven Donate Box is convenient for giving help to people in need. The design included attractive features without compromising the features of the commonly seen donate box. Wearing face masks is recommended as part of personal protective equipment and as a public health measure to prevent the spread of Covid-19.